Why Meta-Organizations Matter: A Response to Lawton et al. and Spillman. (April 2018) - Berkowitz, Héloïse; Bor, Sanne
In a recent issue in this journal, Lawton et al. and Spillman argue for the importance of studying trade associations, also referred to with the broader term meta-organization . They discuss why meta-organizations matter and why more research is needed on the topic. We fully concur with the authors that meta-organizations constitute an inflating, diverse, and undeniable phenomenon of collective action among organizations and that collective scholarly efforts are necessary to improve our understanding of meta-organizations in their multiplicity. In this article, we shed some light on a body of work already investigating the matter. They constitute what we call the "European School" of meta-organization. We show the relevance of this recent European work for the US–UK-oriented trade association research and aim to bridge the gap between these research traditions by proposing a common research agenda on key topics of resources, forms' differentiation, coopetition, and their role in sustainability governance.